Metallicity Determination in Seyfert 2 AGNs - Monteiro, A. F. (2019)
Aims: To study calibrations of line ratios that can estimates metallicities of galaxies even in large redshift where the measurement of faint emission lines is not easy to obtain. Methods: We use the Cloudy Code to build a grid of photoionization models with lines ratios from the UV and, we compare with a sample of 77 object AGNs Seyfert 2. Results: We build semi-empirical calibrations between the metallicity of studied objects and the rest-frame intensity of the line ratios Nv λ1240 / Heii λ1640, C43=log[(Civ λ1549 + Ciii] λ1909) / Heii λ1640] and Ciii] λ1909 / Civ λ1549.